2020
DOI: 10.1016/j.vetmic.2019.108511
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity and immunogenicity of a new strain of porcine epidemic diarrhea virus containing a novel deletion in the N gene

Abstract: A B S T R A C TSince late 2010, highly virulent PEDV G2-genotype strains have emerged globally extracting heavy losses on the pork industries of numerous countries. We investigated the characteristics of a field strain of PEDV (PEDV strain SH) isolated from a piglet with severe diarrhea on a farm in Shanghai China. Whole genome sequencing and analysis revealed that the SH strain belonged to subtype G2b and has a unique 12-aa deletion (aa 399-410) including the antigenic epitope NEP-1C9 (aa 398-406) of the N pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 39 publications
1
13
1
Order By: Relevance
“…It can be seen that all 56 PEDV isolates were divided into two main phylogroups ( Figure 1 ), Group I (including G1a and G1b) and Group II (including G2a, G2b, and G2c). This was in agreement with the findings of previous reports showing two classical divergent clades ( Hsueh et al, 2020 ; Wang X.W. et al, 2020 ).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…It can be seen that all 56 PEDV isolates were divided into two main phylogroups ( Figure 1 ), Group I (including G1a and G1b) and Group II (including G2a, G2b, and G2c). This was in agreement with the findings of previous reports showing two classical divergent clades ( Hsueh et al, 2020 ; Wang X.W. et al, 2020 ).…”
Section: Resultssupporting
confidence: 94%
“…The only accessory protein ORF3 has ion channel activity ( Wang et al, 2012 ), and was found beneficial to virus proliferation ( Wang et al, 2012 ; Ye et al, 2015 ; Si et al, 2020 ). Phylogenetic analysis showed that PEDV could be divided into two genotypes (G1 and G2) and five subgenotypes (G1a, G1b, G2a, G2b, and G2c) based on complete sequence of S gene ( Fan et al, 2017 ; Hsueh et al, 2020 ; Wang H. et al, 2020 ; Wang X.W. et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…MK841495.1), SH (GenBank accession no. MK841494.1) [ 18 ], and CV777 (GenBank accession no. AF353511.1) strains were maintained in our laboratory and passaged in Vero cells with 2.5% trypsin.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that M protein is involved in virion assembly, budding, and host innate immune induction ( Utiger et al, 1995 ). The PEDV N protein is a highly conserved protein that consists of 441aa and is involved in the survival of the virus ( Wang et al, 2020c ).…”
Section: The Genome Structure and Function Of Porcine Enteric Coronav...mentioning
confidence: 99%